Reading Habits and Integration of Technology in Understanding English Texts: A Case Study of EFL Students - Adimawati Helingo (Journal of English Language Teaching, Linguistics, and Literature Studies, 2021)
AbstractThis study aims at exploring how students’ interest in reading books using technology and exploring how technology affects students’ reading habit. Type of design used in this study is quantitative and using questionnaire as the main instrument. In general, it can be said that the level of student interest in reading is still relatively low. Most students think that they were not the kind of students who spend a lot of time reading about English. The technology that develops in the context of learning and reading comprehension shows students' interest in integrating their reading interests using mobile phone and laptops.Keywords: Interest in reading, reading habits, technology